Breathlessness services as a new model of support for patients with respiratory disease. (February 2018) - Bausewein, Claudia; Schunk, Michaela; Schumacher, Philipp; Dittmer, Julika; Bolzani, Anna; Booth, Sara
The complexity of breathlessness in advanced disease requires a diversity of measures ideally tailored to the individual patient needs. 'Breathlessness services' have been systematically developed and tested to provide specific interventions and support for patients and their carers. The aim of this article is (1) to identify and describe components of breathlessness services and (2) to describe the clinical model of one specific service in more detail. This article is based on a systematic review evaluating randomized controlled trials (RCTs) and quasi-RCTs which examine the effectiveness of services aiming to improve breathlessness of patients with advanced disease. The Munich Breathlessness Service (MBS) is described in detail as an example of a recently set-up specialist service. Five service models were identified which were tested in six RCTs. Services varied regarding structure and composition with face-to-face meetings, some with additional telephone contacts. Service duration was median 6 weeks (range 2–12 weeks). Involved professions were nurses, various therapists and, in two models, also physicians. The breathing–thinking–functioning model was targeted by various service components. The MBS is run by a multi-professional team mainly with physicians and physiotherapists. Patients are seen weekly over 5–6 weeks with an individualized management plan. Breathlessness services are a new model for patients with advanced disease integrating symptom management and early access to palliative care.